The Effect Of Company Characteristics On The Disclosure Of Sustainable Reports In LQ45 Companies - Widarti Widarti; Sari Mustika Widyastuti; Triana Agustini; Deva Jordhy (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The aim of this research is to determine the influence of company characteristics as seen from company size, profitability and leverage on the disclosure of sustainability reports in LQ45 companies listed on the Indonesia Stock Exchange. This type of research uses associative research methods. The sample in this research was 42 LQ45 companies listed on the Indonesia Stock Exchange in 2018-2022 which were taken using the purposive sampling method. Based on the results of research on company size, profitability and leverage have a simultaneous effect on the disclosure of sustainability reports in LQ45 companies listed on the Indonesia Stock Exchange, while partially only profitability has an insignificant effect on the disclosure of sustainability reports in LQ45 companies listed on the Indonesia Stock Exchange.